Minimization of AND-EXOR expressions using rewrite rules - Brand, D.; Sasao, T. (IEEE Trans. Comput, 1993)
Conditions for generating optimal two-level AND-EXOR representations using rewrite rules are considered. Four results are presented. First, it is shown that a necessary condition for obtaining minimality is a temporary increase in the size of expressions during minimization. Second, a sufficient condition for obtaining minimality that consists of adding certain two rules to rule sets proposed in the literature is given. Third, transformations that allow the minimization of an expression to proceed by minimizing a transformed expression instead are defined. Fourth, it is determined experimentally that the above three theoretical results lead to better benchmarks results as well.< >